Access to citizenship in the State of Bahia: rebuilding the paths through public platform technologies in Brazil (Research, Society and Development, 2021)
This article sought to analyze citizenship in Brazil, in its aspects of access and enjoyment, having the state of Bahia as a reference, through the work of Prado (2017). Authors have stated that citizenship has been marked by selectivity, on these grounds. Thus, conceptually, social citizenship was used in Marshall (1967), with the principles of equality, freedom and autonomy of participation and enjoyment on the part of individuals. In this sense, access and enjoyment are elementary issues. Thus, the problem is to unveil whether, in addition to public platforms and the postal platform, the extrajudicial services platform can also be an instrument that the Brazilian State has to expand the offer of access to citizenship services, with a more specific focus on the document “Identity Card (CI)” certifier. The objective is to analyze the platform of extrajudicial services, aiming to understand the resources available, to facilitate access to citizenship, for the Identity Card (CI) service. The research is justified because it found in Prado (2017), a study that points to the weaknesses in the provision of services (certifying documents) and the options for expanding services for the population of the state of Bahia. The research has a descriptive/exploratory nature operationalized through comparative analysis. As a result, it was found that there is a broad platform for citizen service (extrajudicial services), with public faith, already implemented by Brazil for a longer time, but in the state of Bahia, only from 2017 onwards, with full capacity to provide access to various services for citizenship, however, another platform little explored by the State.